Promoting justice, human rights and conflict resolution through international law : liber amicorum Lucius Caflisch = La promotion de la justice, des droits de l'homme et du règlement des conflits par le droit international - Kohen, Marcelo G.; Caflisch, Lucius, 1936- (Martinus Nijhoff Publishers, 2007)
Published on the occasion of Judge Lucius Caflisch's retirement from a distinguished teaching career at the Graduate Institute of International Studies of Geneva, this book covers different fields in which Judge Caflisch has excelled in his various capacities. It contains contributions, both in English and French.